Equity in clinical practice requires organisational and system-level change – The role of nurse leaders. Issue 3 (June 2021) - Truong, Mandy; Bourke, Chris; Jones, Yomei; Cook, Olivia; Lawton, Paul
ABSTRACT: Background: In the International Year of the Nurse and Midwife 2020, nurses in Australia and around the world are being encouraged to lend their voices to lead change. The COVID-19 global health crisis has highlighted the critical role of nurses in our community in ensuring that the challenges to our health care system are being met and overcome. It has also brought attention to existing health inequities in our community, in particular the poorer health of refugees, some culturally and linguistically diverse communities and Aboriginal and Torres Strait Islander peoples. Aim: To call on nurses and nurse leaders to take greater action to improve health equity. Methods: This paper presents a discussion with regard to the importance of equitable and safe clinical practice and the urgent need to address organisational and system-level barriers to the provision of equitable health care. Findings: Clinicians' abilities and capacities to provide equitable care is ultimately shaped by health care organisations and the broader historical, political, social and economic context of our community. Discussion: Equity should not only be reflected in clinical practice, but also in organisational policies and procedures, embedded in key performance indicators and supported by adequate funding and resources. Conclusion: Systemic inadequacies are likely to be further amplified during times when the health system is under additional pressure. Nurses and nurse leaders should take this opportunity to reflect upon the integral role they play in addressing organisational and system-level change to ensure equity in health care delivery. We call on nurse leaders and the nursing profession to lead us all to a more equitable health care system and society.